Production and assessment of the biodegradation and ecotoxicity of xylan- and starch-based bioplastics - Abe, Mateus Manabu [UNESP] (2022)
Developing novel renewable (and preferably biodegradable) materials has become recurrent due to the growing concerns with environmental impacts of high volumes of plastic waste produced from oil-based sources over the past decades. This study aimed at developing bioplastics from a mixture of starch and xylan in variable ratios, and the combined effect of α-cellulose and holocellulose extracted from sugarcane bagasse added to the process. The disintegration of bioplastics was evaluated in both soil and composting. The ecotoxicity analyses with Saccharomyces cerevisiae, Bacillus subtilis and seeds of Cucumis sativus were conducted after disintegration. All formulations based on 5% (w/v) of total polysaccharides were dried at 30 °C and resulted in homogeneous and non-brittle bioplastics. The composting results showed that all bioplastic formulations disintegrated in 3 days, whereas the 25/75% (xylan/starch, w/w) formulation vanished in soil within 13 days. The ecotoxicity data showed no inhibition of microbial growth after biodegradation, yielding 100% of seed germination. Despite the positive influence of the bioplastic degradation on the root and hypocotyl growth, temporary inhibition of C. sativus tissues exposed to soil washing (10 days of disintegration) was observed. The study demonstrated that xylan/starch bioplastics result in non-ecotoxic biodegradable materials.